2007
DOI: 10.1093/pcp/pcm044
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis TEOSINTE BRANCHED1-LIKE 1 Regulates Axillary Bud Outgrowth and is Homologous to Monocot TEOSINTE BRANCHED1

Abstract: Key message Tulip vegetative reproduction. Abstract Tulips reproduce asexually by the outgrowth of their axillary meristems located in the axil of each bulb scale. The number of axillary meristems in one bulb is low, and not all of them grow out during the yearly growth cycle of the bulb. Since the degree of axillary bud outgrowth in tulip determines the success of their vegetative propagation, this study aimed at understanding the mechanism controlling the differential axillary bud activity. We used a combine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
227
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 214 publications
(243 citation statements)
references
References 38 publications
12
227
0
4
Order By: Relevance
“…3). Growth of axr1 and tir1 afb1 afb2 afb3 auxin response mutant plants in medium containing GR24 also led to an inhibition of shoot bud outgrowth, whereas the tbl1/brc1 mutant, which is thought to act downstream of strigolactone response (Aguilar-Martínez et al, 2008;Finlayson, 2008), showed no response to strigolactone treatment, as expected (Fig. 3B).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…3). Growth of axr1 and tir1 afb1 afb2 afb3 auxin response mutant plants in medium containing GR24 also led to an inhibition of shoot bud outgrowth, whereas the tbl1/brc1 mutant, which is thought to act downstream of strigolactone response (Aguilar-Martínez et al, 2008;Finlayson, 2008), showed no response to strigolactone treatment, as expected (Fig. 3B).…”
Section: Discussionsupporting
confidence: 82%
“…GR24 again significantly reduced branching in axr1 and also in tir1 afb1 afb2 afb3 mutant plants (P , 0.001 by Student's t test). Branching in the Arabidopsis branched1/teosinte branched1-like1 (brc1/tbl1) mutant, which is mutated in a gene encoding a TCP transcription factor that is thought to function downstream of auxin and SMS perception (Aguilar-Martínez et al, 2008;Finlayson, 2008), was not reduced by GR24 (Fig. 3B).…”
Section: Strigolactone Reduces Branching In Auxin Response Increased mentioning
confidence: 99%
“…Second, double mutant combinations constructed in diverse species, including Atbrc1 max3, Atbrc1 max4, Psbrc1 rms1, and fc1 d17 (Aguilar-Martínez et al, 2007;Minakuchi et al, 2010;Braun et al, 2012), consistently show branching phenotypes that resemble the corresponding SL-deficient single mutant. Additional support for this hypothesis is also available from Arabidopsis and pea, where expression of AtBRC1 and PsBRC1 is reduced in SL mutants (Aguilar-Martínez et al, 2007;Finlayson, 2007;Braun et al, 2012) and PsBRC1 expression is enhanced by SL treatment (Braun et al, 2012). However, in rice, SL regulation of FC1 expression is not observed, and overexpression of FC1 in the d3 mutant only partially rescues the branching phenotype (Minakuchi et al, 2010).…”
mentioning
confidence: 89%
“…Genetic studies in Arabidopsis, pea, and rice implicate orthologs of the maize Teosinte Branched1 (Tb1) transcription factor (Doebley et al, 1997) as a key downstream target of SL signaling. In all three species, mutants of Tb1 orthologs, Atbrc1 (for branched1) and Atbrc2 of Arabidopsis (Aguilar-Martínez et al, 2007;Finlayson, 2007), Psbrc1 of pea (Braun et al, 2012), and fine culm1 (fc1) of rice (Minakuchi et al, 2010), cause increased branching phenotypes. In Arabidopsis, AtBRC1 and AtBRC2 function as integrators for phytochrome regulation of branching (Finlayson et al, 2010).…”
mentioning
confidence: 99%
“…In monocot and eudicot species, the TB1-like genes inhibit bud outgrowth in response to several dormancy-inducing hormonal and environmental signals, suggesting a role as an integrator of signals controlling the dormancy versus outgrowth fates of an axillary bud (Kebrom et al, 2006;Aguilar-Martínez et al, 2007;Finlayson, 2007;Martín-Trillo et al, 2011). In sorghum, dormancy induced by shading was associated with changes in expression of SbTB1, although dormancy induced by defoliation was not.…”
mentioning
confidence: 99%